The Effect of Oxytocin Massage on Uterine Involution in Postpartum Mothers at Tpmb R, Purwakarta Regency in 2024 - Lailatun Lailatun (Riviera Publishing, 2025)
The reproductive health of adolescent girls is prone to disruption due to lifestyle, stress, and lack of understanding of menstrual health. Herbal plants are widely used as an alternative to help with hormonal balance and address menstrual cycle disorders. To determine the effect of herbal plant consumption on improving reproductive health in adolescent girls. Pre-experimental research design with one group pretest-posttest approach. Sample: 30 students of SMK Bhakti Asih who met the inclusion criteria. Intervention: consumption of herbal plants (e.g., sour turmeric, red ginger, and temulawak) for 4 weeks. Data were analyzed using paired t-tests. The[A1] average reproductive health score increased significantly (p < 0.05). The majority of respondents experienced improvements in the menstrual cycle, decreased dysmenorrhea, and increased knowledge about reproductive health. Consumption of herbal plants is effective in improving reproductive health in adolescent girls. It is recommended that schools provide education and assistance in herbal consumption.